2019
DOI: 10.1371/journal.pone.0223920
|View full text |Cite
|
Sign up to set email alerts
|

Lack of detection of Candida nivariensis and Candida bracarensis among 440 clinical Candida glabrata sensu lato isolates in Kuwait

Abstract: Occurrence of Candida nivariensis and Candida bracarensis, two species phenotypically similar to Candida glabrata sensu stricto, in human clinical samples from different geographical settings remains unknown. This study developed a low-cost multiplex PCR (mPCR) and three species-specific singleplex PCR assays. Reference strains of common Candida species were used during development and the performance of mPCR and singleplex PCR assays was evaluated with 440 clinical C. glabrata sensu lato isolates. The interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 82 publications
5
23
0
Order By: Relevance
“…PCR-sequencing of ITS region of rDNA identified 23 different haplotypes among 51 isolates including 16 isolates with unique haplotypes. The data are consistent with a recent study showing that the ITS region of rDNA varies considerably among C. glabrata strains 33 . None of the clinical isolate produced creamy white growth on CHROMagar Candida or yielded an amplicon of ~299 bp which is characteristic of C. bracarensis strains or an amplicon of ~411 bp which is characteristic of C. nivariensis strains in PCR assay 33 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PCR-sequencing of ITS region of rDNA identified 23 different haplotypes among 51 isolates including 16 isolates with unique haplotypes. The data are consistent with a recent study showing that the ITS region of rDNA varies considerably among C. glabrata strains 33 . None of the clinical isolate produced creamy white growth on CHROMagar Candida or yielded an amplicon of ~299 bp which is characteristic of C. bracarensis strains or an amplicon of ~411 bp which is characteristic of C. nivariensis strains in PCR assay 33 .…”
Section: Discussionsupporting
confidence: 93%
“…The genomic DNA from the isolates was extracted by the rapid boiling method using Chelex-100 or by using Gentra Puregene Yeast DNA extraction kit (Qiagen, Hilden Germany) used according to kit instructions and as described previously 58 . Molecular identification was performed by PCR amplification of internal transcribed spacer (ITS) region of rDNA by using mCGLF, mCNIF, mCBRF and mCGCR primers and detection of amplicons by agarose gel electrophoresis, as described previously 33 . The identity of 51 selected isolates was also confirmed by sequencing of ITS region of rDNA by using panfungal primers, as described previously 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four isolates of C. glabrata sensu lato were analyzed by PCR-RFLP and sequencing of the ribosomal ITS and all the strains were identified as C. glabrata sensu stricto. Several studies have investigated the presence of rare cryptic species of the glabrata complex and have not been able to prove their presence [60][61][62]. Whereas, other studies have reported C. nivariensis and C. bracarensis but with a very low prevalences [26,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four isolates of C. glabrata sensu lato were analyzed by PCR-RFLP and sequencing of the ribosomal ITS and all the strains were identified as C. glabrata sensu stricto. Several studies have investigated the presence of rare cryptic species of the glabrata complex and have not been able to prove their presence [62][63][64]. However, other studies have reported C. nivariensis and C. bracarensis but with very low prevalences [28,65,66].…”
Section: Discussionmentioning
confidence: 99%